Responsabilidad social empresarial y su relación con la satisfacción laboral en la empresa Electro Oriente S.A. año 2023 - Ramos Chávez de Young, Gloria Greisy (2024)
The social commitment of companies today is an aspect that generates value and allows society's recognition of business activity, a situation that must be addressed with the purpose of formulating viable improvement alternatives, the study proposes with a general objective to determine the relationship that exists between corporate social responsibility and job satisfaction in the company Electro Oriente S.A. year 2023, with the participation of 81 collaborators and data collection through a 24-question questionnaire with a statistical reliability of Cronbach's alpha 0.863, a quantitative approach was applied, a non experimental correlational design and a significant and positive relationship of 0.702 in Pearson's Rho, with a significance value of 0.000 between corporate social responsibility and employee job satisfaction, the company's commitment to socially responsible practices is directly associated with higher levels of job satisfaction, than a correlation moderate positive between social responsibility and the significance of the task, indicating that the increase in efforts in social responsibility translates into an improved perception of the importance of work responsibilities, which presents a moderate positive correlation between social responsibility and working conditions. work suggests that commitment to responsible practices positively influences the improvement of the work environment and that there is a moderate positive relationship between social responsibility and personal recognition, which demonstrates that business commitment to social responsibility translates into a higher perception of recognition on the part of employees, highlighting the importance of valuing individual contributions in a socially responsible context.